New bedside test for monitoring anticoagulation during hemodialysis - Eiswirth, Georg; Walch, Stefan; Bommer, Jürgen (Artificial organs, 1998)
Heparin therapy in patients can be monitored bedside during dialysis treatment by activated partial thromboplastin time (APTT) measurements using portable coagulation monitors. We verified the efficacy of the CoaguChek Plus System (Boehringer Mannheim, GmbH, Mannheim, Germany) for this purpose. The first series of results was obtained using CoaguChek Plus APTT controls (Level 1 and Level 2) on 3 instruments. The coefficients of variation (CVs) were found to be in the range of 3.6 to 5.0% based on results per instrument (n = 20) and per control level (n = 60). The second series of results was obtained using whole blood drawn from the arterial lines of patients during dialysis treatment. Three determinations out of 1 ml of fresh whole blood gave an overall mean CV of 4.9% from the 123 samples tested. Samples were taken before the onset of heparin treatment, 2 h after treatment was started, and at the end of treatment. The CoaguChek Plus APTT measurements were compared to measurements made using laboratory routine method STA APTT (Boehringer Mannheim GmbH) with results from 104 whole blood samples. Regression analysis according to Passing and Bablok showed good correlation (r = 0.885) and good agreement (y = 0.997x− 6.6) between both methods. Ease of use, excellent performance, reliability, and rapid availability of results within 3 min make the CoaguChek Plus APTT measurements suitable for monitoring patients during dialysis.
Elektronische Reproduktion der Druck-Ausgabe 4. Januar 2002
Gesehen am 08.05.2024